Origin of the Elements Constituting the Universe and Thermonuclear Ignition of Dark Galaxies - Herndon, J. Marvin (European Journal of Applied Sciences, 2025)
Galaxies are prominent features as deep into the universe as astronomers can observe. Among the vast number of galaxies, there are only a few prominent morphologies, suggesting a commonality of formative conditions. Galaxies and the origin of elements heavier than hydrogen and helium are inexplicable within the current foundations of astrophysics which are based upon stellar ignition by gravitational collapse, galaxy formation from luminous stars, and abrogation of scientific standards. Here I present evidence for a fundamentally different understanding that began with the realization that thermonuclear reactions in stars, as in hydrogen bombs/devices, are ignited by nuclear fission chain reactions, and ultimately that dark stars in dark galaxies are ignited by nuclear matter jetted out from the galactic center. The luminous stars of galaxies are evidence of the paths of galactic jets that contacted and seeded dark stars with fissionable elements that ignited their thermonuclear fusion reactions. The nuclear matter of the galactic jets, I posited, is the principal origin and source of elements heavier than hydrogen and helium. The spherical assemblage of un-ignited dark stars maintains the dynamical stability of the pattern of luminous stars as required by the velocity dispersions and rotation curves evidenced by Vera C. Rubin.